1287. Pharmacokinetics, Safety, and Tolerability of Nacubactam after Single Coadministration with β-Lactams in Japanese Healthy Subjects. (31st December 2020) - Asano, Masayo; Sato, Hiroki; Morita, Jun; Ishiwata, Kazuya; Kondo, Kenichiro
Abstract: Background: A single administration of nacubactam (NAC) with concomitant β-lactams in Japanese healthy subjects was conducted to assess pharmacokinetics (PK), safety, and tolerability of NAC in coadministration with cefepime (FEP), aztreonam (ATM), meropenem (MEM), or piperacillin (PIP). Methods: The administration period included Period I, Period II, and Period III where NAC alone, concomitant drug alone, NAC and concomitant drug were administered by 1hour-IV infusion in each period. The dose of each drug tested was 2 g of NAC, FEP, ATM, MEM and 4 g of PIP and 8 subjects were administered in each cohort (32 subjects in total). Results: Plasma NAC concentrations and NAC urinary excretion rate after coadministration with each concomitant drug were similar to those of administration of NAC alone. The PK parameter of NAC showed the similar value both after administration of NAC alone and after concomitant administration with each concomitant drug. Based on these findings, it was confirmed that coadministration of NAC with FEP, ATM, MEM or PIP did not affect the PK of NAC. Plasma concentrations and urinary excretion rate of FEP, ATM, MEM or PIP after coadministration of each concomitant drug with NAC were similar to those of administration of each concomitant drug alone. The PK parameter of each β-lactam tested showed the similar value both after administration of β-lactam alone and after concomitant administration with NAC. Based on these finding, it was confirmed that coadministration of each concomitant drug with NAC did not affect the PK of FEP, ATM, MEM and PIP. As for the safety, there was no serious adverse event, all of TEAEs reported were mild in severity and judged to be "not related". Conclusion: It was confirmed that single coadministration of NAC with FEP, ATM, MEM, or PIP did not affect the both PKs of NAC and β-lactams, and was safe and well-tolerated in Japanese healthy subjects. Disclosures: Masayo Asano, BS, Meiji Seika Pharma Co., Ltd. (Employee) Hiroki Sato, BS, Meiji Seika Pharma Co., Ltd. (Employee) Jun Morita, PhD, Meiji Seika Pharma Co., Ltd. (Employee) Kazuya Ishiwata, MS, Meiji Seika Pharma Co., Ltd. (Employee) Kenichiro Kondo, PhD, Meiji Seika Pharma Co., Ltd. (Employee)